Primary sclerosing cholangitis: diagnostic and therapeutic problems - Gotthardt, Daniel; Chahoud, Fadi; Sauer, Peter (Digestive diseases, 2011)
Progressive destruction of bile ducts in primary sclerosing cholangitis (PSC) may lead to end-stage liver disease, portal hypertension and liver failure. The diagnosis of PSC is made by characteristic multifocal stricturing and dilation of intrahepatic and/or extrahepatic bile ducts observed by cholangiography. Magnetic resonance cholangiography is considered to have comparable accuracy to endoscopic retrograde cholangiography (ERC) in the diagnosis of PSC, but its accuracy is limited in early stages of PSC. Up to 60% of patients with PSC develop a dominant stricture of the intra- or extrahepatic biliary tree. Patients may present with jaundice, pruritus or ascending cholangitis. Therefore, in patients with an increase in serum bilirubin and/or worsening pruritus, progressive bile duct dilation on imaging studies and/or cholangitis seen via ERC, it is recommended to exclude a dominant stricture. However, in a considerable number of patients without symptoms, a dominant stricture can be detected on the cholangiogram. The cholangiographic findings and the clinical presentation make it difficult to distinguish PSC from cholangiocarcinoma. The accuracy in the distinction between these two conditions is still rather disappointing, despite the combined use of imaging, endoscopic biopsy, and cytology. Medical, endoscopic, and surgical therapies aim to slow the progression of the disease. It is generally agreed upon that patients with symptoms from dominant strictures like cholangitis, jaundice, pruritus or worsening biochemical indices are candidates for endoscopic therapy. Although the best therapeutic endoscopic approach for these patients is still under discussion, a number of reports have documented clinical and radiographic improvement in patients following endoscopic dilation with or without placement of a biliary stent. Furthermore, indirect evidence by retrospective studies suggests that endoscopic therapy may improve survival.
Gesehen am 08.07.2022